The Small Area Health Statistics Unit: a national facility for investigating health around point sources of environmental pollution in the United Kingdom. Issue 4 (August 1992) - Elliott, P; Westlake, A J; Hills, M; Kleinschmidt, I; Rodrigues, L; McGale, P; Marshall, K; Rose, G
Abstract : STUDY OBJECTIVE–The Small Area Health Statistics Unit (SAHSU) was established at the London School of Hygiene and Tropical Medicine in response to a recommendation of the enquiry into the increased incidence of childhood leukaemia near Sellafield, the nuclear reprocessing plant in West Cumbria. The aim of this paper was to describe the Unit's methods for the investigation of health around point sources of environmental pollution in the United Kingdom. DESIGN–Routine data currently including deaths and cancer registrations are held in a large national database which uses a post code based retrieval system to locate cases geographically and link them to the underlying census enumeration districts, and hence to their populations at risk. Main outcome measures were comparison of observed/expected ratios (based on national rates) within bands delineated by concentric circles around point sources of environmental pollution located anywhere in Britain. MAIN RESULTS–The system is illustrated by a study of mortality from mesothelioma and asbestosis near the Plymouth naval dockyards during 1981-87. Within a 3 km radius of the docks the mortality rate for mesothelioma was higher than the national rate by a factor of 8.4, and that for asbestosis was higher by a factor of 13.6. CONCLUSIONS–SAHSU is a new national facility which is rapidly able to provide rates of mortality and cancer incidence for arbitrary circles drawn around any point in Britain. The example around Plymouth of mesothelioma and asbestosis demonstrates the ability of the system to detect an unusual excess of disease in a small locality, although in this case the findings are likely to be related to occupational rather than environmental exposure.